Attitude of the Mango Growers towards Global Gap Certification in Konkan Region - Waghmode, Y. J., Hardikar D. P.; Radhika Bhongale (Indian Journal of Extension Education, 2018)
This study was conducted to know the attitude of the mango growers towards Global Gap Certification. Study was conducted in Ratnagiri and Sindhudurg districts of Konkan region of Maharashtra state, which contributes nearly 70 per cent area under mango in the state.The Ratnagiri and Sindhudurg districts were purposively selected for the present study.Profile of the mango growers were 59.00 per cent of the respondents had ’graduation’ education, 72.00 per cent of the respondents had ’medium’ annual income, up to ` 5,33,115/- to 25, 86,885/-. Thus 49.00 per cent of the respondents were having ’medium’ area under mango cultivation, 74.00 per cent of the respondents were having ’medium’ mass media exposure. 77.00 per cent of the respondents were having ’medium’ extension contact. Majority (54.00 %) of the respondents were in the ’high’ market orientation category. Majority (51.00 %) of the respondents belonged to ’high’ risk orientation category. Majority (53.00 %) of the respondents had ’high’ economic motivation. Nearly three-fifth (58.00 %) of the respondents were in ’high’ category. More than three-fifth (63.00 %) of the respondents were found in ’favourable’ category of attitude towards Global Gap certification